Comparisons of clinical impacts on individuals with Brugada electrocardiographic patterns defined by ISHNE criteria or EHRA/HRS/APHRS criteria: a nationwide community-based study. (2nd January 2018) - Chen, Ching-Yu Julius; Juang, Jyh-Ming Jimmy; Chen, Ying-Hsiang; Wu, I-Chien; Hsu, Chih-Cheng; Wu, Ray-Chin; Chen, Kwo-Ching; Liaw, Wen-Jin; Tsai, Tsung-Lung; Lin, Lian-Yu; Hwang, Juey-Jen; Ho, Li-Ting; et al.
Abstract: Introduction: Identifying Brugada electrocardiographic pattern (BrP) early is crucial to prevent sudden cardiac death. Two different diagnostic criteria proposed by International Society for Holter and Noninvasive Electrocardiography (ISHNE) and Heart Rhythm Society/European Heart Rhythm Association/Asia-Pacific Heart Rhythm Society (HRS/EHRA/APHRS) were widely used in clinical practice. The difference in prevalence and prognosis of BrP by applying the two different criteria was never studied before. Methods: This study was prospectively conducted in a nationwide large-scale stratified random sampling community-based cohort (HALST) from Han Chinese population in Taiwan from December 2008 to December 2012. We compared the prevalence and prognosis of BrP defined by the two diagnostic criteria. Results: A total of 5214 adults were enrolled (2530 men) with mean age of 69.3 years. Four had spontaneous type 1 BrP (0.077%). By the HRS/EHRA/APHRS criteria, 68 individuals have type 2 BrP (1.30%) and 101 have type 3 BrP (1.94%) whereas by the ISHNE criteria, 46 individuals exhibited type 2 BrP (0.88%). When applying the ISHNE criteria, the number of individuals with BrP decreased by 71%. However, all-cause mortality and cardiovascular mortality were not different between individuals with or without BrP, irrespective of the criteria used. Conclusions: The two different criteria may impact the diagnostic yield of individuals with BrP, but do not affect the prognosis of the individuals with BrP. Key messages: Comparing with the use of HRS/EHRA/APHRS criteria, the number of individuals with Brugada ECG patterns was decreased by 71% when applying the ISHNE criteria. The prognosis of individuals with Brugada ECG patterns defined by 2012 ISHNE or 2013 HRS/EHRA/APHRS criteria were not different.